Improvement on synthesis of hexagonal close-packed au nanosheets - Yu, Yue. (2012)
This paper commences with the newly-discovered HCP crystal structure of gold nanosheets on graphene oxide and the relevant synthetic techniques. A series of hypotheses are made to deduce the mechanism on how different concentrations of ethanol and oleylamine (OAM) and quality of graphene oxide influence the final quality and size of the HCP gold nanosheets. Control experiments combined with serveral analytical techniques have been systematically carried out to determin the best synthetic parameters, such as reagent concentrations, solvent compositions, and volume ratio of GO. At last, furture direction and new ways of studies are recommended.